A Retrospective Snapshot of American Zen in 1973 - Baroni, Helen J. (Contemporary buddhism, 2020)
In the early 1970s, Zen in the United States remained a fledgling new religious movement, characterised by small, informal meditation groups or living room sanghas, and only a handful of larger practice centres in major metropolitan areas. Existing groups were experimenting, tentatively exploring possibilities to adapt Zen for an American context; groups’ continued survival was precarious. In retrospect, the American Zen movement was actually on the cusp of four decades of dramatic growth and change. This paper analyses data preserved in an unpublished study from 1973, and provides an overview of basic patterns such as membership size, geographical distribution, lineage affiliations and the place of teachers. It identifies and profiles the basic types of Zen organisations and their stage of institutional development, with special attention to group longevity, identifying factors that supported future growth and those that placed groups at the greatest risk for dissolution.